The effect of sexual counseling based on the EX-PLISSIT and BETTER models on the sexual satisfaction of infertile women following assisted reproductive treatment failure - Akram Rahimi Shandiz; Fatemeh Zahra Karimi; Raziyeh Masoumi; Seyed Reza Mazlom (Tehran University of Medical Sciences, 2024)
Background & Aim: Considering that a decline in sexual satisfaction after assisted reproductive treatment failure can cause a decrease in the overall quality and satisfaction of life, the present study was conducted to compare the effect of sexual counseling based on EX-PLISSIT and BETTER models on the sexual satisfaction of infertile women following the failure of assisted reproductive technologies. Methods & Materials: This randomized clinical trial, conducted in 2022, involved 66 infertile women who had experienced unsuccessful assisted reproductive treatments and were referred to the Milad Infertility Center of Imam Reza (AS) Hospital in Mashhad, Iran. The participants were divided into two intervention groups - EX-PLISSIT and BETTER - and received individual sexual counseling across four weekly sessions, comprising two face-to-face and two virtual sessions. Data were collected using the Sexual Satisfaction Scale for Women (SSSW) and subsequently analyzed using SPSS software version 25, through chi-square, independent t-tests, Mann-Whitney, and Wilcoxon tests. Results: After the intervention, there were no statistically significant differences in the total scores of sexual satisfaction and its components between the two groups (P>0.05), with the exception of relational anxiety (P=0.021). Intra-group comparisons revealed a significant increase in the total scores of sexual satisfaction and its components within each group after the intervention, as compared to before the intervention (P<0.05). Conclusion: Sexual counseling utilizing the EX-PLISSIT and BETTER models was found to be an effective, affordable, and side-effect-free method in enhancing sexual satisfaction among infertile women after the failure of assisted reproductive methods, particularly by addressing relational anxiety. Clinical trial registry: IRCT20210211050324N1